2021
DOI: 10.1038/s42003-021-01649-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 specific antibody and neutralization assays reveal the wide range of the humoral immune response to virus

Abstract: Development of antibody protection during SARS-CoV-2 infection is a pressing question for public health and for vaccine development. We developed highly sensitive SARS-CoV-2-specific antibody and neutralization assays. SARS-CoV-2 Spike protein or Nucleocapsid protein specific IgG antibodies at titers more than 1:100,000 were detectable in all PCR+ subjects (n = 115) and were absent in the negative controls. Other isotype antibodies (IgA, IgG1-4) were also detected. SARS-CoV-2 neutralization was determined in C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 51 publications
(49 reference statements)
9
91
2
1
Order By: Relevance
“…24 Similarly, Dogan and colleagues reported a positive correlation between level of care required and elevated SARS-CoV-2-specific antibody levels and neutralization activity in a study of 115 adult participants. 25 Supporting this finding, several other groups reported lower humoral immune responses in patients with mild or asymptomatic disease, including a complete lack of detectable levels of circulating SARS-CoV-2-specific immunoglobulins in some cases. [26][27][28][29] In contrast, we observed similar levels of SARS-CoV-2-specific IgM, IgG, and IgA antibodies and neutralizing activity up to 4 months after acute infection in asymptomatic and mildly symptomatic children.…”
Section: Discussionmentioning
confidence: 59%
“…24 Similarly, Dogan and colleagues reported a positive correlation between level of care required and elevated SARS-CoV-2-specific antibody levels and neutralization activity in a study of 115 adult participants. 25 Supporting this finding, several other groups reported lower humoral immune responses in patients with mild or asymptomatic disease, including a complete lack of detectable levels of circulating SARS-CoV-2-specific immunoglobulins in some cases. [26][27][28][29] In contrast, we observed similar levels of SARS-CoV-2-specific IgM, IgG, and IgA antibodies and neutralizing activity up to 4 months after acute infection in asymptomatic and mildly symptomatic children.…”
Section: Discussionmentioning
confidence: 59%
“…However, there was significant overlap of Ab levels between the two groups such that it could not distinguish mild from severe illness. Other studies corroborated these findings with binding and neutralizing Abs, but the numbers were small, and timing of sample collection was late in disease course (25,26 18.20155374). In addition, previous studies may have underestimated the magnitude of Ab response in severe patients because of a well-established, yet often overlooked, phenomenon known as the prozone effect.…”
Section: Sars-cov-2 Serologymentioning
confidence: 77%
“…As has also been reported in a few independent studies 24,25 , we observed comparable and robust IgG responses to spike RBD and NTD in both naïve and previously infected people after full immunization with an mRNA vaccine 24,25 . Previously, we and others have shown that levels of RBD antibodies correlated well to the magnitude of the neutralizing antibodies in symptomatic SARS-CoV-2 infections [19][20][21][22]26 . Among convalescent plasma donors, who recovered after symptomatic infections, 80% had detectable levels of live virus-neutralizing antibodies 27 ; of those with binding anti-RBD IgG over 1:160 titers, 95% displayed live virus-neutralization.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that the levels of RBD binding antibodies correlated to the SARS-CoV-2 neutralizing antibody titers [19][20][21][22] . To understand the relationship between neutralizing antibodies and spike binding antibodies after mRNA vaccination, we measured live virus SARS-Cov-2 neutralizing titers in 37 paired samples comprising 15 previously infected and 22 naïve individuals after vaccine doses 1 and 2 (Figure 3).…”
Section: Naïve Individuals Develop Weaker Neutralizing Antibodies Than Previously Infected Individualsmentioning
confidence: 99%